miR-21 and miR29-a: Potential Molecular Biomarkers for HPV Genotypes and Cervical Cancer Detection - Zamani, Sara; Hosseini, Seyed M.; Sohrabi, Amir (MicroRNA, 2020)
Background and objective: This study aimed to assess miR21 and miR-29a diagnostic usefulness for HPV infection and Cervical Cancer (CC) detection. Methods: miRs extraction has been performed on HPV-positive, CC and negative control of 43, 50 and 46 individuals, respectively. The expression level of miRs has been analyzed using Real-Time RT-PCR. Results: There was a correlation between the expression of miRs and the Receiver Operating Characteristic (ROC) analysis in CC and HPV-positive patients. Conclusion: The correlation between expressions of miRs is notable. ROC curve analysis could be applied in molecular diagnostic exposure for CC related to HPV infections.
Keywords: HPV